(untitled) (Revista de Estudos da Linguagem, 2024)
This article aims to analyze the discourse of disciplinary power articulated with the discourse of regulatory power in the chronicle Tanta gente, by Eneida de Moraes, elucidating the ways of constituting the subjects, the control of the bodies of individuals, as well as the control of the massifying body. To carry out this discussion, we selected some parts from the chronic that manifest the discursive construction of subjects who do not allow themselves to be inserted without questioning in the objectification/ subjectification processes. Thus, the work consisted of two parts. In the first, we approach some theoretical reflections on the foucautian concepts of discipline, biopolitics and biopower; in the second part, we analyze how these power strategies are present in the eneidian chronic and target the subjects in stigmatized groups. The analysis shows that the characters are constituted under various forms of coercion, namely, exclusion, rejection and abandonment.